Diagnosis dan Tata Laksana Sepsis Maternal - Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno; Atmanagara, Dikho (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Maternal sepsis is a common and potentially preventable cause of direct maternal death globally. A barrierto further progress has been the lack of consensus on the definition of maternal sepsis. Recognition and treatment of maternal sepsis are often delayed due to the physiological adaptations of pregnancy and vague or absent signs and symptoms during its initial presentation. Over the past decade, our understanding of sepsis has evolved and maternal early warning systems have been developed in an effort to help providers promptly identify and stratify parturients who are at risk. In addition, new consensus definitions and care bundles have recently been published by the World Health Organization and the Surviving Sepsis Campaign to facilitate earlier recognition and timely management of sepsis. Standardizing the criteria for maternal sepsis optimizes clinical finding. It may facilitate the evaluation of the role of different clinical parameters and biomarkers in the diagnosis, earlier recognition and management of maternal infection and sepsis. Further work is required to develop an international consensus on the criteria for diagnosing maternal sepsis and any associated organ dysfunction. In this narrative review, we summarize the available evidence about sepsis and provide an overview of the research efforts focused on maternal sepsis to date.